Severe headache as the sole presenting symptom of COVID-19 pneumonia: A case report - Kimambo, Henrika (Interdiscip Neurosurg, 2020)
The spectrum of symptoms of COVID-19 continues to expand as more clinical observations are reported. Neurological manifestations including headache are increasingly described. However, headache as the sole presenting symptom of COVID-19 pneumonia has not been reported. We describe a patient in Tanzania who experienced severe headache for seven days before the onset of other symptoms of COVID-19 that led to her isolation, diagnosis, and treatment.